Environmental and Socio-economic Impacts of Salinity Intrusion in the Coastal Area: A Case Study on Munshigong Union, Shymnagor, Satkhira - Hoque, Md. Al-Amin; Saika, Ummeh; Sarder, Bidhan Chandra; Biswas, Kowshik Kumar (Jahangirnagar University Environmental Bulletin, 2013)
Jahangirnagar University Environmental Bulletin, Vol.2, 41-49, 2013 DOI: http://dx.doi.org/10.3329/jueb.v2i0.16329